Enceladus: Cassini observations and implications for the search for life - Parkinson, C. D.; Liang, M. -C.; Hartman, H.; Hansen, C. J.; Tinetti, G.; Meadows, V.; Kirschvink, J. L.; Yung, Y. L. (CCSD, 2007)
International audience Aims:The recent Cassini discovery of water vapor plumes ejected from the south pole of the Saturnian satellite, Enceladus, presents a unique window of opportunity for the detection of extant life in our solar system. Methods: With its significant geothermal energy source propelling these plumes >80 km from the surface of the moon and the ensuing large temperature gradient with the surrounding environment, it is possible to have the weathering of rocks by liquid water at the rock/liquid interface. For the cases of the putatively detected salt-water oceans beneath the ice crusts of Europa and Callisto, an isolated subsurface ocean without photosynthesis or contact with an oxidizing atmosphere will approach chemical equilibrium and annihilate any ecosystems dependent on redox gradients unless there is a substantial alternative energy source. This thermodynamic tendency imposes severe constraints on any biota that is based on chemical energy. On Enceladus, the weathering of rocks by liquid water and any concomitant radioactive emissions are possible incipient conditions for life. If there is CO, CO2 and NH3 present in the spectra obtained from the plume, then this is possible evidence that amino acids could be formed at the rock/liquid interface of Enceladus. The combination of a hydrological cycle, chemical redox gradient and geochemical cycle give favorable conditions for life. Results: We discuss the search for signatures of these species and organics in the Cassini UVIS spectra of the plume and implications for the possible detection of life.